BEING AS A SYMBOLIC REALITY: A SOCIOCULTURAL CROSS-SECTION OF THE ANALYSIS - Юлія БРОДЕЦЬКА (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The study focuses on the consideration of the symbolic nature of being, presented both at the level of the culture of society and at the level of the human symbolic nature. It is noted that the world cannot be understood exclusively empirically. It is symbols that can explain everything that cannot be explained by the laws of nature. After all, the essence of human knowledge is completely revealed through them. The focus of the article is on the study of the ancient interpretation of the nature of symbolism. This tradition is most thoroughly revealed in Plato’s concept of eidos. Introduced into scientific circulation by the ancient tradition of Heraclitus, Anaxagoras, Democritus, Plato, and Aristotle, symbolism establishes a philosophical coordinate system of thinking. This system reveals the real nature of being and highlights the epistemological potential of its analysis. Eidos, idea, form – those elements of symbolic reality that project the relief of the material world. Eidos, idea – is the ideal beginning, the archetype of a thing, which underlies all categories of being. Both “idea” and “eidos” represent aspects of the ideal-objective nature of meaning. However, if the idea is the archetype that we carry in our souls, then eidos is the logical structure of this idea. This means that eidos has a differential nature, and idea – an integral nature. Ideas-eidos are those constituents on the basis of which, according to Plato, the material world is born. Eidos form the world and are outside it. They manifest in time, but themselves are outside of time. They are unchanging, eternal, unlike things in the material world, which appear and perish. According to Plato, knowledge of the thing essence is not reduced only to sensuality – «correct thought» or «the connection of correct thought with content». In this sense, the process of cognition is revealed as communication (κοινόνία). That is, the interaction between the eidos of an object and the human soul, the result of which is the imprint of an idea in our soul – noema. Such Platonic reflection lays the foundations of the methodological platform within which the religious philosophical tradition unfolds. Within the framework of the latter, the semantic basis of being is “living knowledge” (G.Shpet, S.Frank), “holistic knowledge”, truth. In turn, man himself acts as a certain symbolic reality that responds to the ideal nature of being. Since it is through the symbol that the essence is revealed, and not the imprint of the world in the human imagination. Through the symbol, man discovers the world around him, and therefore himself.